Metamaterial antennas for cognitive radio applications - Raslan, Ahmed Rajaie (AUC Knowledge Fountain, 2013)
Cognitive radio is one of the most promising techniques to efficiently utilize the radio frequency (RF) spectrum. As the Digital Video Broadcasting-Handheld (DVB-H) band is targeted (470-862 MHz), the size of the antenna becomes challenging. Metamaterial concept is used as a miniaturization technique. Two antennas are designed, fabricated and measured. The first one achieved multiband operation by loading it with a metamaterial unit cell. These bands are controlled by engineering the dispersion relation of the unit cell. The second one, which is a 2-lumped elements loaded antenna, achieved wideband operation through the entire DVB-H band with a planar size of 5Ãƒâ€”2 cm^2. A model is proposed to explain, through simple numerical simulations and an optimization algorithm, the behavior of these component loaded antennas (which are equivalent to metamaterial inspired electrically small antennas).